Sirenophila ovis-atra a new species of maritime teloschistaceae from the southern hemisphere - Søchting, Ulrik; Søgaard, Majbrit Zeuthen; Sancho, Leopoldo G.; Frödén, Patrik; Arup, Ulf (J. Lendemer, 2016)
A new species, Sirenophila ovis-atra is described from maritime rocks of southern Patagonia, the Falkland Islands and Macquarie Island, where it grows in the upper part of the black ‘Verrucaria-zone’, most often on members of the genus Hydropunctaria. It is so far the only known species of Sirenophila in South America, a genus that is particularly prominent on the coasts of Australia.